Highlights from the Latest Advances in Psychiatry meeting. Issue 4 (2nd May 2017) - David, Felix
Abstract : The 16th Latest Advances in Psychiatry Symposium took place in March at the Royal College of Physicians, presenting current perspectives on obsessive‐compulsive disorder, adherence to oral antipsychotics and recognising body dysmorphic disorder. Felix David reports